2007
DOI: 10.1007/s00221-007-1204-9
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory integration for orienting responses in humans requires the activation of the superior colliculus

Abstract: Animal studies have shown that the superior colliculus (SC) is important for synthesising information from multiple senses into a unified map of space. Here, we tested whether the SC is a critical neural substrate for multisensory spatial integration in humans. To do so, we took advantage of neurophysiological findings revealing that the SC does not receive direct projections from short-wavelength-sensitive S cones. In a simple reaction-time task, participants responded more quickly to concurrent peripheral (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 51 publications
7
49
0
Order By: Relevance
“…Another possibility is that the differing products of multisensory and unisensory integration properly reflect the pooling of information from two independent sources in the former, and the covariance between information sources in the latter. In either case, these data speak to an important caveat in the interpretation of multisensory enhancements as being produced by a "redundant targets effect" (e.g., Miller, 1982;Gondan et al, 2005;Leo et al, 2007;Lippert et al, 2007;Sinnett et al, 2008), as redundant targets from the same sensory modality do not yield equivalent enhancements either physiologically or behaviorally.…”
Section: Discussionmentioning
confidence: 88%
“…Another possibility is that the differing products of multisensory and unisensory integration properly reflect the pooling of information from two independent sources in the former, and the covariance between information sources in the latter. In either case, these data speak to an important caveat in the interpretation of multisensory enhancements as being produced by a "redundant targets effect" (e.g., Miller, 1982;Gondan et al, 2005;Leo et al, 2007;Lippert et al, 2007;Sinnett et al, 2008), as redundant targets from the same sensory modality do not yield equivalent enhancements either physiologically or behaviorally.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, psychophysical interactions between vision and audition are not present in experimental paradigms involving colours (cf. Leo et al 2008;Arieh and Marks 2008). Figure 5 shows that in synaesthetic pairings between auditory nouns and visual adjectives, eighty percent are constituted by auditory nouns modified by visual adjectives referring to brightness (see examples 4-5), whereas only ten percent are constituted by auditory nouns modified by visual adjectives referring to colour, 29 e.g.,:…”
Section: The Results Of a Corpus-based Analysis And Parallels With Mumentioning
confidence: 99%
“…Furthermore, they provided evidence that audiovisual train ing, presumably by SC stimulation, may induce more organized patterns of visual exploration due to an implementation of efficient oculomotor strategies. Leo et al (2008a) have demonstrated that SC is the critical neural substrate for multisensory spatial integration in humans thanks to an experiment in which participants responded to peripheral (extra-foveal) audiovisual stimuli more quickly than to an auditory or visual stimulus alone -the so-called 'redun dant target effect (RTE)'. This was true only when the colour of the stimulus was red and not purple.…”
Section: Introductionmentioning
confidence: 99%